2017
DOI: 10.1177/0959683617729443
|View full text |Cite
|
Sign up to set email alerts
|

Human-induced changes in fire regime and subsequent alteration of the sandstone landscape of Northern Bohemia (Czech Republic)

Abstract: Multiproxy palaeoecological evidence from a sandstone region in northern Czech Republic was collected to explore the impact of fire disturbances on the decline of the broadleaved forests during the Late Bronze Age (3250-3050 cal. BP). It has been hypothesized that human-accelerated soil leaching affected the nutrient availability in the sandstone area, thus promoting the expansion of oligotrophic-adapted plant communities in the late-Holocene.Little is known about the mechanisms which induced such large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 100 publications
3
21
1
Order By: Relevance
“…, fire is considered a negligible disturbance agent in central European temperateforests. Yet, the results of this study support emerging literature demonstrating that fires have been an important disturbance agent throughout the Holocene in temperate forests (e.g Clark et al, 1989;Bobek et al 2017;Niklasson et al, 2010;Novák et al 2012)…”
supporting
confidence: 87%
See 1 more Smart Citation
“…, fire is considered a negligible disturbance agent in central European temperateforests. Yet, the results of this study support emerging literature demonstrating that fires have been an important disturbance agent throughout the Holocene in temperate forests (e.g Clark et al, 1989;Bobek et al 2017;Niklasson et al, 2010;Novák et al 2012)…”
supporting
confidence: 87%
“…Yet, over the past decade emerging literature has demonstrated that fires have occurred for millennia in central European forested ecosystems (e.g. Clark et al, 1989;Bobek et al 2017;Niklasson et al, 2010;Novák et al 2012). However, crucial parameters of fire regimes i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Fires represent the best recorded disturbance factors in palaeoecological data (Power et al, 2007;Vannière et al, 2016). Identification of significant peaks in charcoal records suggests fire frequency of 250-500 years (Bobek, Svobodová, Werchan, Švarcová, & Kuneš, 2018;Carter et al, 2018) during the middle Holocene in our study region although frequency seems to increase abruptly in recent centuries (Niklasson et al, 2010). However, it should be noted that any quantitative comparison with individual charcoal events lies beyond capabilities of our data, which encompass all disturbance factors showing an overall disturbance regime capturing various disturbance means (see Section 2; Herben et al, 2016).…”
Section: Potential Causes Of Changes In Disturbance Dynamicsmentioning
confidence: 73%
“…(e.g. Bobek et al., 2018; Härtel et al., 2007; Novák et al., 2015; Šída et al., 2014a, 2014b; Svoboda, 2003, 2017; Svoboda et al., 2018). Thanks to these investigations, sandstone landscapes have revealed examples of the extreme and rapid impoverishment of local biota, which was originally attributed to the late Bronze Age colonization and accompanying human impacts and interpreted as environmental collapse (Härtel et al., 2007; Pokorný and Kuneš, 2005), sometimes expressively called the ‘Lusitanian Catastrophe’ (Cílek et al., 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to these investigations, sandstone landscapes have revealed examples of the extreme and rapid impoverishment of local biota, which was originally attributed to the late Bronze Age colonization and accompanying human impacts and interpreted as environmental collapse (Härtel et al., 2007; Pokorný and Kuneš, 2005), sometimes expressively called the ‘Lusitanian Catastrophe’ (Cílek et al., 1996). Recently, anthropogenic forest fires were shown to be an important driver of these dynamics (Bobek et al., 2018).…”
Section: Introductionmentioning
confidence: 99%